Moderasi Beragama Dalam Perspektif Sa’id Hawwa’ Dan Implementasinya Terhadap Nilai Humanisme (Kajian Kitab al-Asas Fi al-Tafsir) - Juniarti, Yevi; Shohib, Muhammad (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2024)
Religious moderation means practicing religion by choosing the middle path, in the sense of not being radical, not extreme, not rigid, and not excessive in dealing with differences in groups that are not the same as ourselves. It also means not being overly excessive in practicing religious teachings to the point of neglecting the surrounding world and disregarding others. Respecting fellow human beings is also embodied in Pancasila, which states "just and civilized humanity," meaning we must respect fellow human beings regardless of race, ethnicity, group, social status, or even religion. In this study, the researcher will discuss the interpretation of religious moderation from the perspective of Sa'id Hawwa' and how the interpretation of moderation is implemented towards humanistic values. The type of research used in this study is library research. In the exploration of verses, the researcher uses a conceptual thematic approach, while the approach used in the interpretation is the thematic figure. The data sources used in this study consist of primary and secondary data. The techniques used in data analysis are descriptive and analytical methods. The results of the research on religious moderation from Sa'id Hawwa's perspective are that Islam has offered the value of moderation to humans. The purpose of this moderation is none other than to unite and respect differences, achieve peace, apply justice in all actions, promote good and prevent evil, and obey the government regardless of race, ethnicity, or even religion. The implementation of the interpretation of moderation verses towards humanistic values is to realize universal human values and teach the protection of human rights for all individuals, regardless of race, ethnicity, group, social status, or even religion. This includes the responsibility to ensure the welfare of all people.